Audience as Community: Corporeal Knowledge and Empathetic Viewing - Wood, Karen (The International Journal of Screendance, 2015)
This essay focuses on community in the form of audiences, and in particular, screendance audiences. A specific focus is given to a collection of screendance experiences from viewing a selection of contemporary dance films. The term screendance is used in this research as suggested by Douglas Rosenberg as "stories told by the body" and "not told by the body." What follows, for this essay, are theories borrowed from the discipline of audience and reception research detailing what we may perceive audiences to be and how the idea of 'audience' as a community may influence the way filmmakers approach the very audiences they hope to reach. Kinesthetic empathy will be used as a framework to understand the pleasures and displeasures that are experienced by the viewer from an embodied perspective. While considering kinesthetic empathy with audience and reception research, the main focus for this essay is nuancing the idea of audiences as a community that is enriched with corporeal knowledge. This knowledge reveals itself as empathetic and sympathetic viewing of the media.